2009
DOI: 10.1111/j.1360-0443.2008.02493.x
|View full text |Cite
|
Sign up to set email alerts
|

Drinking patterns, dependency and life‐time drinking history in alcohol‐related liver disease

Abstract: Aims To examine the hypothesis that increases in UK liver deaths are a result of episodic or binge drinking as opposed to regular harmful drinking. Design A prospective survey of consecutive in-patients and out-patients. Setting The liver unit of a teaching hospital in the South of England. Participants A total of 234 consecutive in-patients and out-patients between October 2007 and March 2008. Measurements Face-to-face interviews, Alcohol Use Disorders Identification Test, 7-day drinking diary, Severity of Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 21 publications
8
55
0
4
Order By: Relevance
“…We have previously reported a mean of 114 cl alcohol/week in patients with alcohol-related cirrhosis. 8 A French study found a mean consumption of 165 cl/week in patients with cirrhosis and 248 cl/week in patients of an MUP on liver-related mortality. The mean intake of 145 cl alcohol/week in our harmful drinking patients with liver disease compares with a mean of 71.4 units for the harmful category of drinkers from the General Lifestyle Survey (2009) 30 used in the Sheffi eld model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously reported a mean of 114 cl alcohol/week in patients with alcohol-related cirrhosis. 8 A French study found a mean consumption of 165 cl/week in patients with cirrhosis and 248 cl/week in patients of an MUP on liver-related mortality. The mean intake of 145 cl alcohol/week in our harmful drinking patients with liver disease compares with a mean of 71.4 units for the harmful category of drinkers from the General Lifestyle Survey (2009) 30 used in the Sheffi eld model.…”
Section: Discussionmentioning
confidence: 99%
“…The study was performed in two cohorts by trained fourth-year medical students using validated alcohol assessment tools, as previously reported. 8 The main study cohort (n=204 in fi nal analysis) was recruited from 16 December 2012 to 1 April 2013 (excluding weekends and university holidays), when undergraduate student researchers were available to attend clinics and liver wards. Researchers had no knowledge of the underlying liver diagnosis before they approached patients.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adding to the confusion is the growing awareness of the role of binge or episodic drinking in ALD, 36,37 which contradicts other reports that it is a steady pattern of drinking daily or near daily heavy drinking which is particularly hazardous. 38 This is likely compounded by confused messages in the popular media 39 and a dearth of widespread and consistent GP-based education and counselling. 40 Possibly arising from this confusion, participants described the difficulty of knowing what they were meant to adhere to in terms of safe drinking, relying instead on very individual definitional criteria and safe drinking guidance grounded in their own beliefs and experiences, and this has been noted elsewhere.…”
Section: Competing Interestsmentioning
confidence: 99%